Hoffmann Photograph MS608_3_8_005 - Walery Lucien (My University, 2013)
Black and white wide group action shot of Hoffmann Girls (and a few male dancers) on stage in costume. Set design is a cityscape. Reverse has "Walery stamp.

Photographer's stamp: "Reproduction interdite copyright PHOTOGRAPHIE Walery9his, Rue de Londres, Paris. Ce portrait ne peut etre reproduit sans ma signature WaleryParis avec un 'W'."
Keywords: Gertrude Hoffmann Company